Calculus: Early Transcendentals 8th Edition

Published by Cengage Learning
ISBN 10: 1285741552
ISBN 13: 978-1-28574-155-0

Chapter 3 - Section 3.5 - Implicit Differentiation - 3.5 Exercises - Page 215: 1


1a. $y'=\frac{9x}{y}$ 1b. $y'=\pm\dfrac{9x}{\sqrt{9x^2-1}}$ 1c. See solution below.

Work Step by Step

1a. $9x^2-y^2=1$. Taking the derivative of both sides we get $18x-2yy'=0$. Solving for $y'$ we get $y'=\frac{9x}{y}$. 1b. Solving for $y$ we get $y^2=9x^2-1$ so $y=\pm\sqrt{ 9x^2-1}$. Then $y'=\pm\frac{1}{2}(9x^2-1)^{-\frac{1}{2}}*18x$ using chain rule. Simplifying, we get $y'=\pm\dfrac{9x}{\sqrt{9x^2-1}}$. 1c. We can see that $y'=\pm\dfrac{9x}{\sqrt{9x^2-1}}=\dfrac{9x}{y}$ since $y$ from part b is $\pm\sqrt{ 9x^2-1}$ which checks out with our answer in part a.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.